Traumatic C1–2 rotatory subluxation with dens and bilateral articular facet fractures of C2: A case report. Issue 13 (March 2018) - Chang, Dong-Gune; Park, Jong-Beom; Jang, Hyuk-Jin
Abstract: Rationale: To the best of our knowledge, this is an extremely rare case of traumatic C1–2 rotatory subluxation associated with multiple C2 fractures. Patient concerns: We report the case of a 63-year-old man with type 2 traumatic C1–2 rotatory subluxation (Fielding and Hawkins classification) associated with type III dens (Anderson and D'Alonzo classification) and bilateral articular facet fractures of C2. This injury occurred as a result of falling down in a drunken state. The patient complained of neck pain and mild degree of torticollis but did not show any neurologic abnormalities. Diagnoses: Plain radiographs of cervical spine showed extensive soft tissue swelling, a fracture fragment, disruption of spinolaminar line at C1–2 level, and bony overlapping of right side lateral joint of C1–2. Two- and three-dimensional reconstructed computed tomography scans clearly demonstrated complicated C1–2 combined injury. The atlantodental interval was normal. Intervention: By skull traction and derotation, closed reduction of C1–2 rotatory subluxation with a type III dens and bilateral articular facet fractures of C2 was successfully achieved. He was managed with halovest fixation for 3 months. Outcomes: At the 1-year follow-up visit solid fusion and improvement of clinical symptoms were achieved without C1–2 instability. Lessons: Despite traumatic C1–2 rotatory subluxation associated with multiple C2 fractures, trial of closed reduction should be considered as the first choice of treatment so as to preserve C1–2 motion.